Application of Logistic Regression Model in Mental Health Evaluation: A Case Study of Farmers Working Under High Voltage Transmission Line (HVTL) - Fatima, Kaniz; Ali, Basit; Khan, Ali; Attayyab Khan, Abdul; Mahnoor (Applied Psychology Review, 2023)
The current study examined the environmental impact of High Voltage Transmission Lines (HVTL) on human health, specifically the psychological health of farmers in Pakistan. The electric and magnetic fields that emanate from HVTL may have adverse effects on human health including psychological disorders. To investigate the probability of psychological disorders among farmers working under HVTL, the current study employed a logistic regression model considering the variables of gender, age, transmission line type, work duration, and prior health conditions. The results showed that women working under HVTL are more vulnerable to psychological disorders than men. Additionally, the probability of psychological disorders increases with age of the farmers, voltage magnitude, and duration of work under HVTL. The Female farmers aged between 46 to 69 years, working under a 220 KV HVTL for up to six hours daily, were at a significantly higher risk of experiencing psychological disorders. These findings highlighted the environmental impact of HVTL on psychological health of the farmers. Moreover, it also highlighted the need for adopting measures to mitigate the risk and protect both the environment and human health.